2016
DOI: 10.1002/jobm.201500738
|View full text |Cite
|
Sign up to set email alerts
|

Raoultellasp. strain L03 fixes N2in association with micropropagated sugarcane plants

Abstract: N2 -fixing bacteria belonging to the genus Raoultella of the family Enterobacteriaceae are widely associated with plants. Raoultella sp. strain L03 was isolated from surface-sterilized sugarcane roots. In this study, we inoculated the strain L03 to microbe-free micropropagated plantlets of the main sugarcane cultivar ROC22 grown in Guangxi, China and determined N2 -fixation and association between strain L03 and sugarcane plants. Inoculation of strain L03 increased plant biomass, total N, N concentration and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Our discovery of diazotrophs in the DSP group classified as Gammaproteobacteria suggested that bacteria of this taxonomic class from the mucilage environment are likely to contribute to the BNF phenotype of Sierra Mixe maize. This is supported by previous studies describing species from enterobacterial genera classified among genomes in the DSP group (Enterobacter, Klebsiella, Kosakonia, Rahnella, and Raoultella) as diazotrophic endophytes associated with cereal crops such as sugarcane, rice, and maize [56][57][58][59][60]. Recent reports demonstrated the successful engineering of a Pseudomonas strain capable of associating with wheat and maize as a diazotrophic endophyte [61], as well as successful growth promotion of maize using a diazotrophic strain of Pseudomonas isolated from the rhizosphere of rice [62].…”
Section: Diazotrophs Formed Three Distinct Nitrogen Fixation Groups Bsupporting
confidence: 83%
“…Our discovery of diazotrophs in the DSP group classified as Gammaproteobacteria suggested that bacteria of this taxonomic class from the mucilage environment are likely to contribute to the BNF phenotype of Sierra Mixe maize. This is supported by previous studies describing species from enterobacterial genera classified among genomes in the DSP group (Enterobacter, Klebsiella, Kosakonia, Rahnella, and Raoultella) as diazotrophic endophytes associated with cereal crops such as sugarcane, rice, and maize [56][57][58][59][60]. Recent reports demonstrated the successful engineering of a Pseudomonas strain capable of associating with wheat and maize as a diazotrophic endophyte [61], as well as successful growth promotion of maize using a diazotrophic strain of Pseudomonas isolated from the rhizosphere of rice [62].…”
Section: Diazotrophs Formed Three Distinct Nitrogen Fixation Groups Bsupporting
confidence: 83%
“…With respect to diazotrophic associations with cereal crops, recent investigation into a diazotrophic strain of R . planticola demonstrated that it was capable of conferring BNF-mediated PGP to sugar cane through endophytic colonization [ 49 ]. While reference genomes for these species exist in GenBank [ 50 ] and the Genome Taxonomy Database (GTDB) [ 51 ] used to classify mucilage isolate genomes in this study, the lack of species level assignment to described species of Raoultella for many mucilage derived Raoultella isolates using WGS similarity indicates the potential genomic novelty for Raoultella associated with Sierra Mixe maize and suggests that strain variation is important for these traits to be conferred in the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, all of K. pneumoniae isolate genomes are predicted to encode the capacity for nitrogen fixation, consistent with previous results (14, 26). The single Raoultella ornithinolytica isolate characterized here also contains the same 16 nif genes; Raoultella species have previously been isolated from sugarcane (27) and have also been demonstrated to fix nitrogen (28).…”
Section: Resultsmentioning
confidence: 90%